RELATIVE EXPOSURE INTENSITY MEASURING APPARATUS AND METHOD - IMAMURA, GENICHI; TSUNEMOTO, HIDEHARU (2008)
Disclosed is a method which comprises the steps of providing a video-signal output device (4), accepting a brightness component of a video signal corresponding to a first position of a subject (1) which is imaged by the video-signal output device (4), correcting a gamma (³) value of the brightness component corresponding to the first position, accepting a brightness component of the image signal corresponding to a second position of the subject (1) which is imaged by the video-signal output device (4), correcting the gamma (³) value of the brightness component corresponding to the second position, calculating a ratio between the gamma-corrected brightness component corresponding to the first position and the gamma-corrected brightness component corresponding to the second position, and displaying the ratio.